2008
DOI: 10.1111/j.1399-0004.2008.00980.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene dosage imbalances in patients with 46,XY gonadal DSD detected by an in‐house‐designed synthetic probe set for multiplex ligation‐dependent probe amplification analysis

Abstract: The development of a testis requires the proper spatiotemporal expression of the SRY gene and other genes that act in a dosage-sensitive manner. Mutations in the SRY gene account for only 10-15% of patients with 46,XY gonadal disorder of sex development (DSD). To enable the diagnostics of deletions and duplications of genes known to be involved in different forms of DSD, we developed a synthetic probe set for multiplex ligation-dependent probe amplification (MLPA) analysis. Here, we report the results from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 35 publications
3
51
1
1
Order By: Relevance
“…region of the NR0B1 gene resulting in incomplete DSS (Barbaro et al, 2008). In contrast, the patient reported here has a breakpoint that is further centromeric, containing the entire NR0B1 gene and control elements and therefore exhibiting complete DSS.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…region of the NR0B1 gene resulting in incomplete DSS (Barbaro et al, 2008). In contrast, the patient reported here has a breakpoint that is further centromeric, containing the entire NR0B1 gene and control elements and therefore exhibiting complete DSS.…”
Section: Discussioncontrasting
confidence: 43%
“…Sex reversal due to Xp21 disomy is rare and has been observed as a result of an interstitial duplication of Xp21, an X;A translocation or an X;Y translocation (Sanlaville et al, 2004;Barbaro et al, 2007Barbaro et al, , 2008Tzschach et al, 2008). The patient reported here is one of a small number of reported cases resulting from an X;Y translocation (Table 3), and the only one that has been resolved at the level of oligonucleotide-based CMA.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Trace data were analyzed using the Gene Mapper v3.7 software and exported to an Excel spreadsheet (Microsoft). Analysis, using peak heights, was performed as described previously (20).…”
Section: Gene Analysesmentioning
confidence: 99%
“…Because XY individuals deleted for DSS develop as males it can be proposed that DAX1 is required for ovarian but not testicular development and that its action should be turned off in XY genital ridge to avoid interference with testis development. 25 A study done in Italy by Barbaro M, et al in 2008 had shown in 46 XY gonadal dysgenesis identified two copy number variations, duplication of DAX1 gene, indicaing that DAX 1 is not required for the development of testis. But recent studies done in mice model suggest that DAX1 is required for the development of testis.…”
mentioning
confidence: 99%